2002
DOI: 10.1002/ijc.10730
|View full text |Cite
|
Sign up to set email alerts
|

The green tea polyphenol, epigallocatechin‐3‐gallate, protects against the oxidative cellular and genotoxic damage of UVA radiation

Abstract: A number of biological activities have been ascribed to the major green tea polyphenol epigallocatechin-3-gallate (EGCG) to explain its chemopreventive properties. Its antioxidant properties emerge as a potentially important mode of action. We have examined the effect of EGCG treatment on the damaging oxidative effects of UVA radiation in a human keratinocyte line (HaCaT). Using the ROS-sensitive probes dihydrorhodamine 123 (DHR) and 2 ,7 -dichlorodihydrofluorescein diacetate (DCFH-DA), we detected a reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 54 publications
3
68
0
1
Order By: Relevance
“…To date only few substances/extracts have been demonstrated to be capable of protecting/suppressing UVA-induced skin cells/ skin injury e.g. carnosic acid 71 , quercetin 72 , epikatechin 74 , epigallokatechin-3-gallate 74,75 or P. leucotomos extract 76 , silymarin 77 and P. vulgaris extract 78 . Considering the latest knowledge about UV radiation it is necessary to look for new substances possessing both UVA and UVB protection.…”
Section: B) Exogenous Photoprotectionmentioning
confidence: 99%
“…To date only few substances/extracts have been demonstrated to be capable of protecting/suppressing UVA-induced skin cells/ skin injury e.g. carnosic acid 71 , quercetin 72 , epikatechin 74 , epigallokatechin-3-gallate 74,75 or P. leucotomos extract 76 , silymarin 77 and P. vulgaris extract 78 . Considering the latest knowledge about UV radiation it is necessary to look for new substances possessing both UVA and UVB protection.…”
Section: B) Exogenous Photoprotectionmentioning
confidence: 99%
“…In addition, because it has recently been reported that DEP or organic DEP extracts induce pro-oxidative and proinflammatory effects in the respiratory tract that can be negated by thiol antioxidants such as N-acetyl cysteine (NAC) (18,19), we also examined whether NAC or another antioxidant, epigallocatechin 3-gallate (EGCG), which is one of the main polyphenolic constituents of green tea (20,21), could neutralize the suppression of IFN-␥ mRNA expression and protein production by DEP. EGCG in addition to NAC significantly recovered the IFN-␥ production by DEP-treated T cells, which suggested the crucial role of oxidative stress in the effects of DEP.…”
mentioning
confidence: 99%
“…2). Since aging is thought to involve the accumulation of oxidative stress, 21,22) it is possible that an age-dependent burden of oxidative stress causes degradation of the immune defense system against the tumor cells. In actual fact, the cytotoxicity of NK cells is known to be dependent on oxidative stress and the activity is often reduced by ROS.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, GT-catechins, especially EGCG, are known to work as potent radical scavengers and show antioxidative effects against various types of oxidative stress. 22,25) Unno et al demonstrated that long-term intake of EGCG water up-regulated the level of antioxidative activity in the serum of aged SAMP10 mice. 26) Thus, we speculated that GT-catechin intake provided protection from the accumulation of oxidative stress and improved the reduced NK activity with age.…”
Section: Discussionmentioning
confidence: 99%